Relationship Between Skin Intrinsic Fluorescence—an Indicator of Advanced Glycation End Products—and Upper Extremity Impairments in Individuals With Diabetes Mellitus. Issue 8 (1st August 2015) - Shah, Kshamata M.; Clark, B. Ruth; McGill, Janet B.; Lang, Catherine E.; Maynard, John; Mueller, Michael J.
Abstract : Background: Accumulation of advanced glycation end products (AGEs) is thought to contribute to limited joint mobility in people with diabetes mellitus (DM), but the relationships among AGEs, shoulder structural changes, movement, and disability are not understood. Objective: The purpose of this study was to determine the differences and relationships among skin intrinsic fluorescence (SIF), a proxy measure of AGEs, biceps and supraspinatus tendon thickness, upper extremity movement, and disability in groups with and without DM. Design: This was a cross-sectional, case-control study. Methods: Fifty-two individuals participated: 26 with type 2 DM and 26 controls matched for sex, age, and body mass index. The main outcome measures were: SIF; biceps and supraspinatus tendon thickness; 3-dimensional peak shoulder motion; and Disability of the Arm, Shoulder and Hand (DASH) questionnaire scores. Results: Mean SIF measurements were 19% higher in the DM group compared with the control group ( P <.05). Biceps tendons (mean and 95% confidence interval [CI]) (4.7 mm [4.4, 5.0] versus 3.2 mm [2.9, 3.5]) and supraspinatus tendons (6.4 mm [5.9, 6.8] versus 4.9 mm [4.4, 5.3]) were thicker and peak humerothoracic elevation (139° [135°, 146°] versus 150° [146°, 155°]) and glenohumeral external rotation (35° [26°, 46°] versus 51° [41°, 58°]) were reduced in the DM group compared with the control group ( P <.05). In the DM group, SIF was correlated to biceps tendon thickness, DASH score, and shoulder motion ( r =.44–.51, P <.05). The SIF score and shoulder strength explained 64% of the DASH scores ( P <.01). Limitations: Because this was a cross-sectional study design, a cause-effect relationship could not be established. Conclusions: Accumulation of AGEs in the connective tissues of individuals with DM appears to be associated with increased tendon thickness and decreased shoulder joint mobility and upper extremity function. Physical therapists should be aware of these possible metabolic effects on structure, movement, and disability when treating people with diabetes.